Benefits of an early identification and diagnosis of permanent bilateral hearing loss. (September 2013) - Newton, Valerie
Abstract: Newborn hearing screening has resulted in hearing loss being detected significantly earlier than previously. Research has shown that there are several areas in which this has changed the outcome for the child concerned and the family, and has indicated that there are advantages accruing for the community at large. In this article, ways in which the early identification and habilitation of a permanent bilateral hearing loss has been beneficial for hearing impaired children for all degrees of impairment are described.